Penggunaan media audio-visual dalam meningkatkan hasil belajar gerakan senam round off - Rahmadani, Ahmad; Daharis; Candra, Oki (UIR Press Bekerjasama dengan International Association of Physical Education and Sports, 2022)
The round off movement is a movement that is quite difficult to demonstrate by students, this is due to the lack of development of floor gymnastics learning, especially the use of learning media. This study aims to determine the effect of using audio-visual media in improving the learning outcomes of round off gymnastics movements. This study involved 42 students as research samples. The method used is an experiment where treatment is carried out in 12 meetings with data analysis techniques using pre tests and post tests. The research instrument used a round off test consisting of three stages: the initial phase, the main phase, and the final phase. Based on the results of the study that there is an effect of using audio-visual media on the learning outcomes of round off gymnastics movements, and there is an increase of about 30%. So based on the results of the study, the use of audio-visual media is effective for improving the learning outcomes of round off gymnastics movements. The results of the study show positive things how the use of audio-visual media can be a solution and alternative in learning floor gymnastics movements, but there are still some limitations. It is hoped that future researchers can develop by increasing the number of sample groups and involving comparison groups so as to get new findings in the field.